Proof of the External World. - Duncan, Steven M. (James Clarke & Co, 2008)
Descartes' attempt to ground the possibility of human knowledge in the existence of God was judged to be a complete failure by his contemporaries. This remains the universal opinion of philosophers to this day, despite thefact that three and a half centuries of secular epistemology ' which attempts to ground the possibility of knowledge either in the unaided human intellect or in natural processes ' has failed to do any better. Further, the leading twentieth century attempts at theistic epistemology reject both the conception of knowledge and the standards of epistemic evaluation that Descarte.